How Orthopaedic Residents Perceive Educational Resources - Wolf, Brian R. (The University of Iowa, 2013)
INTRODUCTION: The educational paradigm for orthopaedic surgeons is shifting from a strictly Operating Room based approach to the addition of simulator- and lab-based models. This study aims to assess resident views on the relative value of orthopaedic educational resources and the value of a cadaver-based arthroscopy skills laboratory. METHOD: A questionnaire assessing beliefs about various orthopaedic educational resources for overall orthopaedic education and surgical skills education was given to all residents in one orthopaedic residency program with a new arthroscopic skills laboratory during a three year period. Forty-one orthopaedic residents from years PGY1 through PGY5 participated. RESULTS: Observation and participation in the OR was the highest ranked learning activity for both overall and surgical skills education. Sessions in the skills lab ranked second for surgical skills education and fourth for overall orthopaedic education. The arthroscopic skills lab was most highly valued for practicing 3-D use of instruments and developing familiarity with equipment. CONCLUSIONS: Orthopaedic trainees highly value operating room experience as the primary resource for education during residency. Orthopaedic trainees have found the addition of a surgical skills training lab for teaching arthroscopic skills a significant benefit to both their overall education and to surgical skills training.